Juxtaposing Design Representations for Creativity - Sutcliffe, Alistair (Human Technology, 2010)
This paper argues that the influence of design rationale on creativity is best achieved by concurrent use of scenarios, prototypes and models. A framework of cognitive affordances is introduced to discuss the merits and limitations of each representation. The paper concludes by discussing how different representations might complement each other in creative scenario-based design.